Lower Leg Fractures in Children and Adolescents—Comparison of Conservative vs. ECMES Treatment - Weber, Birte; Kalbitz, Miriam; Baur, Meike; Braun, Christian Karl; Zwingmann, Jörn; Pressmar, Jochen (Frontiers in Pediatrics, 2021)
Abstract Background: Lower leg fractures are one of the most common fractures in pediatric age. In general, treatment of lower leg fractures is predominantly non-operative, requiring clinical and radiological controls. Nevertheless, it can be observed that in recent years tibial shaft fractures have increasingly been treated surgically. The aim of the present study is to investigate treatment strategies in the context of different fracture types of the lower leg. Methods: In this retrospective chart review, we analyzed 168 children with a diaphyseal fracture of the lower leg admitted to a trauma center between 2005 and 2017. The fractures were classified according to the AO Pediatric Comprehensive Classification of Long Bone Fractures (AO-PCCF). Results: The frequency of fractures based on the AO-PCCF classification was as follows: Simple oblique fracture of the tibia (43.5%, n=73), hereof 32 toddler’s fractures, multifragmentary oblique fracture of the tibia in 14.3% (n=24) and simple oblique fracture of both, tibia and fibula in 18 patients (10.7%). Most pediatric fractures were treated conservatively by cast (n=125). 37 patients received an ECMES, whereas 3 patients were treated with an external fixator and also 3 fractures were stabilized by plate osteosynthesis. Conservatively treated patients were significantly younger (mean age 6.0) compared to patients treated with ECMES (mean age 10.2) or plate osteosynthesis (PO) / external fixator (EF) (mean age 11.3), even if toddler’s fractures (mean age 2.0) are excluded (mean age 7.4). There was no difference in time to full weight-bearing, hospitalization of patients treated with ECMES compared to conservative therapy although ECMES-treated fractures show mor instability. The consolidation time was significantly higher in ECMES treated patients compared to conservative therapy. Conclusion: Pediatric patients (≤4 years) with lower leg fractures most often showed simple oblique fractures of the tibia, half of them toddler`s fractures, which were treated predominantly by conservative therapy. All in all, the consolidation time was longer in intramedullary nailing (ECMES) than in conservative therapy. Nevertheless, time to full weight bearing and duration of cast was the same in both groups, even though ECMES treated fractures show more instability.